The Effect of Bankruptcy Protection on Investment: Chapter 11 as a Screening Device. - Mooradian, Robert M (Journal of Finance, 1994)
Asymmetric information and conflicts of interest between equity and debt holders can force a distressed but efficient firm to liquidate and may enable a distressed inefficient firm to continue. In the extreme, if it is costless for an inefficient firm to mimic an efficient firm in a debt restructuring, efficient and inefficient firms are equally likely to continue or liquidate. This article shows that Chapter 11 procedures impose costs on inefficient firms that would otherwise mimic efficient firms. This separation induces voluntary filing for bankruptcy by inefficient firms and consequently enables efficient firms to continue when they would otherwise be liquidated.